2002
DOI: 10.1089/108076802760116142
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl Cyclase Activity Mediated by β-Adrenoceptors in Immortalized Human Trabecular Meshwork and Non-Pigmented Ciliary Epithelial Cells

Abstract: Non-pigmented ciliary epithelial (NPE) and trabecular meshwork (TM) cells are important in maintaining normal aqueous humor dynamics through the inflow and outflow routes, respectively. The current studies were undertaken to evaluate the ability of several beta-adrenergic receptor agonists to stimulate various antagonists to inhibit cAMP production in cultured immortalized human TM and NPE cells using an automated enzyme immunoassay. Isoproterenol was the most potent agonist in both the NPE and TM cells. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Traditionally, b-adrenergic receptors have been described as modulators of IOP by changing the intracellular levels of cAMP in nonpigmented epithelial cells (Crider and Sharif, 2002). This has permitted the design and discovery of new b-adrenergic receptors antagonists to reduce IOP (Sharif et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, b-adrenergic receptors have been described as modulators of IOP by changing the intracellular levels of cAMP in nonpigmented epithelial cells (Crider and Sharif, 2002). This has permitted the design and discovery of new b-adrenergic receptors antagonists to reduce IOP (Sharif et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that although CB 1 was found to colocalize with adrenergic inputs in the anterior eye, the bulk of CB 1 staining did not overlap with the inputs, suggesting that CB 1 may have additional postsynaptic (or nonsynaptic) functions. Recent work has demonstrated that CB 1 receptors heterodimerize with ␤ 2 AR receptors (Hudson et al, 2010), and because both of these receptors are expressed within the ciliary body epithelium (Straiker et al, 1999;Stamer et al, 2001;Crider and Sharif, 2002), the possibility that CB 1 /␤ 2 AR heterodimerization within the ciliary epithelial cells contributes to the ocular hypotensive properties of cannabinoids cannot be completely ruled out.…”
mentioning
confidence: 99%
“…These SV40-transformed NPCE cells are functionally similar to both untransformed primary NPCE cells (Coca-Prados & Wax, 1986) and epithelial cells of the intact ciliary body (Yantorno et al, 1989), with preservation of ion transport systems (Delamere et al, 1993;Patil et al, 2001) and GPCRs (Coca-Prados & Wax, 1986;Crook et al, 1992;Mitchell et al, 1999;Crider & Sharif, 2002).…”
Section: Cell Culturementioning
confidence: 95%